PROSPECTS FOR THE FORMATION AND DEVELOPMENT OF ARTIFICIAL INTELLIGENCE POLICY IN UZBEKISTAN - Amirova , Shohista (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
Artificial intelligence (AI) is becoming a key driver of global technological and socio-economic transformation. This article examines the prospects for the formation and development of artificial intelligence policy in Uzbekistan. The study analyzes national digital transformation strategies, institutional frameworks, and international experience in AI governance. Particular attention is given to the role of education, infrastructure, and innovation ecosystems in shaping sustainable AI policy. The research identifies key challenges, including limited research capacity, insufficient funding, and the need for regulatory improvements. The findings suggest that strengthening digital infrastructure, investing in human capital, and expanding international cooperation are essential for the effective implementation of AI policy in Uzbekistan.